The effect of biochar amendments on phenanthrene sorption, desorption and mineralisation in different soils - Moreno Jiménez, Eduardo; Aceña-Heras, Sara; Frišták, Vladimír; Heinze, Stefanie; Marschner, Bernd (PeerJ, 2018)
The contamination of soils and waters with organic pollutants, such as polycyclic aromatic hydrocarbons (PAHs), affect a large number of sites worldwide that need remediation. In this context soils amendments can be used to immobilise PAHs while maintaining soil functioning, with biochar being a promising amendment. In this experiment, phenantrene (Phe) was used as a frequent PAH contaminating soils and we studied the effect of three biochars at 1% applications to three different substrates, two agricultural topsoils and pure sand. We evaluated the changes in soil properties, sorption-desorption of Phe, and mineralisation of Phe in all treatments. Phe in pure sand was effectively sorbed to olive pruning (OBC) and rice husk (RBC) biochars, but pine biochar (PBC) was not as effective. In the soils, OBC and RBC only increased sorption of Phe in the silty soil. Desorption was affected by biochar application, RBC and OBC decreased water soluble Phe independently of the soil, which may be useful in preventing leaching of Phe into natural waters. Contrastingly, OBC and RBC slightly decreased the mineralisation of Phe in the soils, thus indicating lower bioavailability of the contaminant. Overall, biochar effects in the two tested soils were low, most likely due to the rather high soil organic C (SOC) contents of 2.2 and 2.8% with Koc values in the same range as those of the biochars. However, OBC and RBC additions can substantially increase adsorption of Phe in soils poor in SOC.
Keywords: Phenathrene; Soil; 14C–labelling; Sorption; Biochar; Mineralisation